Taxonomic Revision of Hibiscus (Malvoideae) of Malvaceae sensu lato in Toor Al-Baha District, Lahej Governorate, Yemen - Al-Hawshabi, Othman Saad Saeed (Journal of natural sciences, life and applied sciences, 2024)
The current study presents a taxonomic revision of the genus Hibiscus subfamily Malvoideae, Malvaceae s.l. in Toor Al-Baha district, Lahij Governorate, Yemen, from May 2009 to November 2021, based on about 44 specimens conducted. Five species were recognized in the study area (H. aristaevalvis, H. deflersii, H. palmatus, H. trionum, H. vitifolius), to study the vegetative and reproductive morphological characteristics, describing them in detail, comparing them, and making it easy to identify the types of the genus studied from the results obtained. The morphological characteristics of the vegetative and reproductive parts were proved to have high taxonomic significance in distinguishing between five species belonging to the genus of Hibiscus. An artificial key to the five species, full species descriptions, photos, updated names, synonymy, and local names. The wing fruit of Hibiscus vitifolius was distinguished from the rest of the species of Hibiscus studied. Also, the results proved that the H. aristaevalvis is clearly distinguished from H. palmatus by several vegetative, flowering, and reproductive characteristics, such as the number of blade lobos (7), the surface beneath the blade covered with stellate hairs densely, the number of epicalyx (10-13), sepals’ length and short style (2-2.5 mm).